2007
DOI: 10.1016/j.ecoleng.2006.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of bio-economic modelling to compare silvoarable, arable, and forestry systems in three European countries

Abstract: Silvoarable agroforestry could promote use of trees on farms in Europe, but its likely effect on production, farm profitability, and environmental services is poorly understood. Hence, from 2001 to 2005, the Silvoarable Agroforestry for Europe project developed a systematic process to evaluate the biophysical and economic performance of arable, forestry, and silvoarable systems in Spain, France, and The Netherlands. A biophysical model called "Yield-SAFE" was developed to predict long-term yields for the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
1
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(115 citation statements)
references
References 18 publications
6
97
1
11
Order By: Relevance
“…Modeling of agroforestry systems in Europe using the Yield-SAFE (YIeld Estimator for Long-term Design of Silvoarable AgroForestry in Europe) model predicted LER values between 1-1.4 for scenarios in Spain, France, and the Netherlands, indicating higher productivity when integrating trees and crops than when grown separately [100]. In another study in Switzerland, agroforestry models focusing on walnut (Juglans hybrid) and wild cherry (Prunus avium) showed that in 12 out of 14 scenarios, mixing crops led to LER measurements higher than one.…”
Section: Benefits Of Agroforestrymentioning
confidence: 99%
“…Modeling of agroforestry systems in Europe using the Yield-SAFE (YIeld Estimator for Long-term Design of Silvoarable AgroForestry in Europe) model predicted LER values between 1-1.4 for scenarios in Spain, France, and the Netherlands, indicating higher productivity when integrating trees and crops than when grown separately [100]. In another study in Switzerland, agroforestry models focusing on walnut (Juglans hybrid) and wild cherry (Prunus avium) showed that in 12 out of 14 scenarios, mixing crops led to LER measurements higher than one.…”
Section: Benefits Of Agroforestrymentioning
confidence: 99%
“…IRR is a mean annual return derived from an investment and expressed in percentage (Graves et al 2007). IRR value indicates an interest rate that can be paid by a business, or in other words, the ability to gain income from the cost invested.…”
Section: Discussionmentioning
confidence: 99%
“…A feasible cultivation business is indicated by the IRR value that is bigger than the interest rate applied at the time when the investment taking place (Graves et al 2007). The interest rate at the time of this study was 6% per year.…”
Section: Financial Feasibility Of Tengkawang Cultivation Modelmentioning
confidence: 99%
“…L' ensemble de la parcelle profite alors des bénéfices agroenvironnementaux liés aux arbres. Les systèmes de culture intercalaire peuvent de plus générer des revenus diversifiés liés à la production de bois (bois d' oeuvre et biomasse) (Graves et al 2007) tout en rédui-sant certaines charges (économies en intrants) (Thevathasan et Gordon 2004, Malézieux et al 2009). Ils permettent ainsi une production intégrée et économiquement rentable.…”
Section: Introductionunclassified